2014
DOI: 10.1186/1465-9921-15-48
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on dendritic cell phenotypes in the airway lumen of patients with COPD

Abstract: BackgroundMyeloid dendritic cells (DCs) are increased in the airway wall of patients with chronic obstructive pulmonary disease (COPD), and postulated to play a crucial role in COPD. However, DC phenotypes in COPD are poorly understood.MethodsFunction-associated surface molecules on bronchoalveolar lavage fluid (BALF) DCs were analyzed using flow cytometry in current smokers with COPD, in former smokers with COPD and in never-smoking controls.ResultsMyeloid DCs of current smokers with COPD displayed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Second, IgA responses were studied in vitro in co-cultures of AECs and B-cells, while other players (e.g. dendritic cells) could be involved [14,15]. Third, the presence of lymphoid follicles in the COPD lung [33] could also, in turn, modify B-cell/immunoglobulin responses to smoke exposure.…”
Section: Both Maturation Of B-cells Into Cd38mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, IgA responses were studied in vitro in co-cultures of AECs and B-cells, while other players (e.g. dendritic cells) could be involved [14,15]. Third, the presence of lymphoid follicles in the COPD lung [33] could also, in turn, modify B-cell/immunoglobulin responses to smoke exposure.…”
Section: Both Maturation Of B-cells Into Cd38mentioning
confidence: 99%
“…These follicles consist of a specific arrangement of B-cells, T-cells, dendritic cells and follicular dendritic cells [11,12]. It has been suggested that dendritic cells, numbers of which are increased in COPD small airways, play an important role in the formation of peribronchial lymphoid follicles in this disease [13][14][15]. B-cells are also key players in adaptive immunity, acting not only as immunoglobulin-producing but also as antigen-presenting cells.…”
Section: Introductionmentioning
confidence: 99%
“…ERT had no significant influence in Fabry patients on mDC or pDC percentage as compared with untreated patients indicating a direct incluence of the disease and or Gb 3 on this cell‐type . The importance of mDC‐s in other obstructive lung diseases is underlined by significantly decreased number of mDC‐s in the small airways and alveoli of COPD patients . As mentioned above, mDC‐s are presented mainly in inflammatory conditions, suggesting these cells may play important role in the development and maintenance of inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…The small airways in COPD contain cDC with heightened expression of chemokine ligand 20 (CCL20), a potential cause of CD8 T-cell activation 43 . In contrast, there is evidence that some aspects of cDC function may be down regulated in COPD with cDC immaturity associated with airway vascularity and expression of angiogenic factors 44 , and reduced expression of the chemokine receptor CCR5 45 . Furthermore, a recent report indicates that CD1c+ DCs from patients with COPD hinder T-cell effector functions and favor the generation of suppressive T cells.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%